‘To All the Gods of Neferusy’ - Ferreres, Romain (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
The unpublished stele of Djehutymes son of Nehemaway presented here is a small monument coming from a region poor in archaeological remains and showing the piety of a man towards the gods of his hometown. The stele’s main interests lie in the unusual depiction of the frog goddess Heqet as well as in the reference to the two cities of Her-wer and Neferusy, thus adding another stone to the building of their relationship as well as their nature.